Improving the writing ability of deaf children through giving rewards in grade 1 SLB Pangudi Luhur West Jakarta - Fridaningtyas, Onik; Suparno, Suparno (ARKA INSTITUTE, 2025)
This study aims to examine the effectiveness of rewarding in improving the writing ability of deaf children in grade 1 of SLB B Pangudi Luhur, West Jakarta. The method used is Class Action Research (PTK) with three cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 10 deaf students aged 6-8 years. Data was collected through observation, writing tests, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results showed that giving rewards in the form of verbal compliments, stickers, and small gifts succeeded in improving students' writing skills, with the average score increasing from 39 in the pre-cycle to 83 in the 3rd cycle. In addition, the number of students who achieved completeness also increased significantly, from 2 students (20%) in the pre-cycle to 8 students (80%) in the 3rd cycle. The implications of this study suggest that rewarding can motivate deaf students to be more active in learning and help them overcome difficulties in writing. Therefore, giving rewards can be used as an effective strategy in learning to write for children with special needs, especially in special schools (SLB). This study also suggests the application of a more individualized and consistent approach to support student development more optimally.